Co-occurrence of Adult ADHD Symptoms and Problematic Internet Use and Its Links With Impulsivity, Emotion Regulation, Anxiety, and Depression - El Archi, Sarah; Barrault, Servane; Brunault, Paul; Ribadier, Aurélien; Varescon, Isabelle (Frontiers in Psychiatry, 2022)
Problematic Internet use (PIU) co-occurs with some psychiatric disorders (i.e., dual diagnosis), especially attention-deficit/hyperactivity disorder (ADHD). The co-occurrence of ADHD and PIU is associated with increased severity of PIU and poorer treatment outcomes. The main objective of this study was to examine the association between PIU and ADHD and the potential mediating role of dimensional psychopathological factors, including anxiety, depression, impulsivity, and emotion regulation, in this relationship. The secondary objective was to identify the predictors of PIU. To achieve these aims, we recruited 532 regular Internet users online from the general adult population. The participants completed an online questionnaire assessing Internet Addiction Test, Hospital Anxiety and Depression Scale, Adult ADHD Self-Report Scale, Emotion Regulation Questionnaire, and Impulsive Behavior Scale. We conducted a multiple regression analysis to determine the predictors of PIU and mediation analyses to identify the psychopathological mediators of the association between ADHD and PIU. PIU was observed in 17.9% of our sample. Self-reported adult ADHD was more prevalent in individuals with PIU compared to without. Individuals with PIU reported significantly higher scores for anxiety and depressive symptoms, impulsivity, and the emotion regulation strategy of expressive suppression. Additionally, they had significantly lower scores on cognitive reappraisal than non-problematic Internet users. The mediation analysis showed that lack of perseverance, positive urgency, and depressive and anxiety symptoms are partial mediators of the relationship between ADHD and PIU. In addition to ADHD, the multiple regression analysis revealed that PIU is also positively predicted by depressive symptoms, positive urgency, lack of perseverance, and expressive suppression, and is negatively predicted by cognitive reappraisal and negative urgency. Our results highlight the significant co-occurrence of PIU and ADHD. This study also provides support for a theoretical model in which impulsivity dimensions, emotion regulation strategies, as well as the tendency to anxiety and depressive symptoms may play a mediating role in this co-occurrence relationship. In summary, the findings emphasize the need to assess these psychological characteristics in problematic Internet users, as they can be a factor of clinical complexity, as well as the importance of targeting them as part of integrated interventions for both ADHD and PIU.